Tradisi Tanem Ari-Ari Ditinjau dari Perspektif Akidah Islam di Desa Pematang Ganjang Kecamatan Sei Rampah Kabupaten Serdang Bedagai - Masnah Masnah (UIN Sumatera Utara, 2021)
This article was written to explore the traditions carried out by some people in carrying out a tradition that has been carried out for generations in Pematang Ganjang village, Sei District. Rampah Serdang Bedagai Regency. Pematang Ganjang village is a village not far from the city center. It makes it easier for people to do things. The government system that is run in this village is a government led by the Village Head who is assisted by the village apparatus. Pematang Ganjang Village is one of the villages located in Sei District. Rampah Serdang Bedagai Regency. The community has various ethnicities, languages, and several different religions, but even though there are many different tribes, languages, and religions, the community still upholds a sense of tolerance and harmony in society. Although the religion in Pematang Ganjang village is predominantly Muslim, however, there are some groups of people who still follow the teachings of their ancestors and are hereditary in nature, resulting in some people committing acts that are contrary to the beliefs of Muslims. Pematang Ganjang has many ethnic groups, including Javanese, Banjarese, Simalungun, Acehnese, Malay, Mandailing, Batak, Karo and Bantenese. And the Javanese tribe is the most widely embraced by the Pematang Ganjang community. This research is expected to be able to open our mindset as readers to better understand and strengthen our hearts and minds towards belief in Allah and not to follow teachings that do not know where they come from and guidelines. We as religious people must be more selective in choosing which one is good and which one is bad. By strengthening our faith and belief, so as not to fall into wrong beliefs.